PENGARUH PENERAPAN MODEL PEMBELAJARAN POE2WE BERBANTUAN MEDIA INTERAKTIF LIVEWORKSHEETS TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Fauziah, Isma; Nurjamil, Dedi; Patmawati, Hetty (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the effect of implementing the POE2WE learning model assisted by Liveworksheets interactive media on students’ mathematical conceptual understanding in probability material. This study employed a quantitative approach with a quasi-experimental method using a Posttest Only Control Group Design. The population consisted of ninth-grade students of SMP Negeri 2 Tasikmalaya in the 2025/2026 academic year. The sample included two classes, namely class IX E as the experimental class and class IX D as the control class, each consisting of 34 students selected using a purposive sampling technique.The research instrument was an essay test measuring mathematical conceptual understanding, which had been tested for validity and reliability. The results showed that the average posttest score of students’ mathematical conceptual understanding in probability material in the experimental class was 18.68, while the control class obtained 12.15. Hypothesis testing using an Independent Sample t-Test revealed that the calculated t-value was 7.883 with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. This indicates that students who learned using the POE2WE learning model assisted by Liveworksheets had better mathematical conceptual understanding in probability material than those who learned using the Problem Based Learning (PBL) model. Furthermore, the effect size analysis yielded η² = 0.485, which is categorized as a large effect. In conclusion, the implementation of the POE2WE learning model assisted by Liveworksheets interactive media has a significant and strong effect on students’ mathematical conceptual understanding in probability material.